A novel nitrogenous coumarin: The promising antiviral therapy against white spot syndrome virus in the culture of shrimp seedlings - Huan Wang; Xu Zhang; Lei Liu; Li-Peng Shan (Aquaculture Reports, 2024)
White spot disease (WSD), attributed to the white spot syndrome virus (WSSV), represents a substantial danger to the international shrimp sector, resulting in considerable losses in both production and economic terms. Nevertheless, there are currently no approved therapeutic measures to control the outbreak. This study involved the synthesis of 15 new compounds for the assessment of their anti-WSSV efficacy in Litopenaeus vannamei post-larvae. Among these compounds, N-(4-methyl-2-oxo-2H-chromen-7-yl)acetamide (P13) exhibited a maximum antiviral response of > 90 %, with a median effective concentration (EC50) < 12 mg/L, making P13 the most promising antiviral compound. In the cases where the larvae were simultaneously incubated with WSSV and P13, as well as where the larvae were first infected with WSSV and then treated with P13, the replication of WSSV was significantly inhibited. However, pre-treatment with P13 had minimal impact on WSSV multiplication, suggesting a potential therapeutic effect. Simultaneously, the cumulative mortality rate of WSSV-infected post-larvae decreased in the presence of P13. After the shrimp larvae were infected with WSSV, continuously changing the aquacultural water containing DMSO resulted in a mortality rate of 80 % at 120 hours post-infection (hpi); whereas continuously changing the aquaculture water containing P13 resulted in a mortality rate of 45 %. Given that P13 remains stable in farmed water for up to two days, it is recommended to regularly replace the medication to eliminate the virus threat. In conclusion, P13 demonstrates a positive anti-WSSV activity and holds potential for further development as an antiviral therapy against WSSV infection.